Personalized alignment techniques better restore the native trochlear groove compared to systematic alignment techniques in total knee arthroplasty - Orsi, Alexander D.; Shatrov, Jobe; Plaskos, Christopher; Kreuzer, Stefan (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2024)
Purpose The relationship between constitutional coronal alignment and implant positioning on trochlear groove restoration in total knee arthroplasty (TKA) is poorly understood. This study aimed to determine whether the choice of alignment philosophy significantly affects the restoration of the trochlea groove. Methods Sixty‐one imageless robotic TKAs performed by a single orthopaedic surgeon were retrospectively reviewed. In each case, the entire native trochlea was digitized to generate the native femoral anatomy, and implants were planned according to a functional alignment (FA) technique. Final implant position was recorded using the validated bone resection planes from the navigation system. Simulated femoral component positions were generated according to previously described alignment techniques: mechanical alignment (MA), gap balancing (GB), kinematic alignment (KA), restricted kinematic alignment (rKA) and restricted inverse kinematic alignment (riKA). Trochlear angle (TA), trochlear under/overstuffing and mediolateral sulcus offset were compared between the six simulated alignment techniques, as well as the final implanted technique. Further analyses investigated the effect of preoperative coronal alignment on trochlear position. Comparisons were assessed with an analysis of variance and Welch's t‐tests or Wilcoxon's rank‐sum tests with Bonferroni corrections. Results The implanted and simulated techniques all resulted in greater TA valgus compared to the native groove (p < 0.001). The implanted technique, KA and rKA were closer to the native TA than GB, MA and riKA (p > 0.001). All alignment philosophies understuffed the native trochlea groove. KA and rKA understuffed less than all other techniques (p < 0.001), and GB understuffed more than all other techniques (p < 0.001). In extension, all techniques shifted the trochlear sulcus laterally, while in flexion, they medialized it. These effects were most prominent in GB and MA. Conclusion Personalized alignment techniques such as KA and rKA, which consider variations in individual anatomy, best restore the native patellar groove compared to systematic alignment techniques when using a standardized femoral component. Level of Evidence Level III, retrospective review.